2015
DOI: 10.7573/dic.212269
|View full text |Cite
|
Sign up to set email alerts
|

Resource use and outcomes associated with initiation of injectable therapies for patients with type 2 diabetes mellitus

Abstract: Introduction:Management of type 2 diabetes mellitus (T2DM) often requires intervention with oral and injectable therapies. Across National Health Service (NHS) England, injectable therapies may be initiated in secondary, intermediate or primary care. We wished to understand resource utilization, pathways of care, clinical outcomes, and experience of patients with T2DM initiated on injectable therapies.Method:We conducted three service evaluations of initiation of injectable therapies (glucagon-like peptide-1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, the CHOICE study took place in several European countries excluding the UK and included secondary care contacts . In a study carried out by Brice and colleagues, initiation with a GLP‐1 receptor agonist was less costly than with a BI because of lower staff costs and fewer clinic visits . Mean cost for GLP‐1 receptor agonists was £43.81 in primary care, £243.49 in intermediate care and £518.99 in secondary care, whereas mean cost for BI was £473.63 in intermediate care and £571.11 in secondary care …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the CHOICE study took place in several European countries excluding the UK and included secondary care contacts . In a study carried out by Brice and colleagues, initiation with a GLP‐1 receptor agonist was less costly than with a BI because of lower staff costs and fewer clinic visits . Mean cost for GLP‐1 receptor agonists was £43.81 in primary care, £243.49 in intermediate care and £518.99 in secondary care, whereas mean cost for BI was £473.63 in intermediate care and £571.11 in secondary care …”
Section: Discussionmentioning
confidence: 99%
“…11 In a study carried out by Brice and colleagues, initiation with a GLP-1 receptor agonist was less costly than with a BI because of lower staff costs and fewer clinic visits. 30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also the opinion of specialists in this study who suggested education of PCPs on insulin initiation and easy-to-follow guidelines as focal points that may lead to more initiations in primary care. The perceived complexity may also be a factor for the increased time taken to initiate insulin therapy [8]. This iterates that appropriate education and guidance could further support GPs and potentially reduce the time and lower comfort level with insulin initiation in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a metabolic disorder, with features including high blood sugar and insulin deficiency-induced impaired glucose tolerance and/or islet dysfunction (Brice et al, 2015). Diabetic vascular disease is the leading cause of death and disability in diabetic patients; 30-40% of the patients are subject to at least one vascular complications after 10 years (Tavintharan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%